2006
DOI: 10.1159/000096101
|View full text |Cite
|
Sign up to set email alerts
|

Caries Patterns in Primary Dentition in 3-, 5- and 7-Year-Old Children: Spatial Correlation and Preventive Consequences

Abstract: This study aimed to contribute to the descriptive information of oral health status in the primary dentition, especially concerning the distribution and spatial correlation of lesions. Data were obtained from two surveys. In the Signal-Tandmobiel® project 4,468 7-year-old children in Flanders (Belgium) were selected by a stratified clustered random sample. In the Tandje de Voorste – Smile for Life (TDV) project, data were obtained from 1,291 3-year-old and 1,315 5-year-old children. The children were examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 49 publications
1
28
0
5
Order By: Relevance
“…The study did not show precise symmetry between equivalent surfaces on the left and right sides of the mouth but found that symmetry existed within groups of sites with similar susceptibility to caries. A recent evaluation of deciduous teeth in 7,074 children aged 3-7 years [Vanobbergen et al, 2007] concluded that associations of caries experience at the population level appeared to follow a symmetrical pattern, but at an individual level, when using the same method as Hujoel et al [1994], the study found similar results, i.e. that caries lesions tend to cluster on 1 side of the mouth.…”
mentioning
confidence: 87%
“…The study did not show precise symmetry between equivalent surfaces on the left and right sides of the mouth but found that symmetry existed within groups of sites with similar susceptibility to caries. A recent evaluation of deciduous teeth in 7,074 children aged 3-7 years [Vanobbergen et al, 2007] concluded that associations of caries experience at the population level appeared to follow a symmetrical pattern, but at an individual level, when using the same method as Hujoel et al [1994], the study found similar results, i.e. that caries lesions tend to cluster on 1 side of the mouth.…”
mentioning
confidence: 87%
“…The regularities in caries distribution with regard to teeth, sites and groups of sites were also found [12-16]. The three possible patterns were evaluated: random, aggregated and regular, however, the hypothesis that teeth were randomly infected by caries was rejected.…”
Section: Introductionmentioning
confidence: 99%
“…Its prevalence varies considerably in different populations from 4% in Sweden by 11.7% in England, 50.5% in Lithuania to above 80% in Native Americans or Kosovo. [1][2][3][4] The incidence of tooth decay in children at this age ranges from 0.4 to 3.86.…”
mentioning
confidence: 99%
“…9,10 The pattern of caries in primary dentition changes with age, as in 3-year-old children the upper incisors are the most frequently affected by caries, while in older children the lower molar teeth, which may suggest a connection with the timing of tooth eruption and their time of being in the oral cavity. 11,12 The aim of the study was to evaluate the pattern of early childhood caries in children at the age of 3.…”
mentioning
confidence: 99%